1999
DOI: 10.1074/jbc.274.50.35676
|View full text |Cite
|
Sign up to set email alerts
|

PHR1 Encodes an Abundant, Pleckstrin Homology Domain-containing Integral Membrane Protein in the Photoreceptor Outer Segments

Abstract: We cloned human and murine cDNAs of a gene (designated PHR1), expressed preferentially in retina and brain. In both species, PHR1 utilizes two promoters and alternative splicing to produce four PHR1 transcripts, encoding isoforms of 243, 224, 208, and 189 amino acids, each with a pleckstrin homology domain at their N terminus and a transmembrane domain at their C terminus. Transcript 1 originates from a 5-photoreceptorspecific promoter with at least three Crx elements ((C/T)TAATCC). Transcript 2 originates fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 86 publications
1
17
0
Order By: Relevance
“…Evictin-1 can localize to rhodopsin-laden, postGolgi membranes in photoreceptor cells, suggesting that the protein may be involved in postGolgi traffi cking of membranes ( 202 ). PHR1 is present in outer segments and binds to transducin ␤ ␥ subunits but does not bind to inositol phosphates; however, PI lipids were not tested ( 204 ). The PH domain of PHR1 is most similar to that of Akt, which we found in the ROS ( 135 ).…”
Section: Phosphoinositides In Retina Structure and Functionmentioning
confidence: 64%
See 1 more Smart Citation
“…Evictin-1 can localize to rhodopsin-laden, postGolgi membranes in photoreceptor cells, suggesting that the protein may be involved in postGolgi traffi cking of membranes ( 202 ). PHR1 is present in outer segments and binds to transducin ␤ ␥ subunits but does not bind to inositol phosphates; however, PI lipids were not tested ( 204 ). The PH domain of PHR1 is most similar to that of Akt, which we found in the ROS ( 135 ).…”
Section: Phosphoinositides In Retina Structure and Functionmentioning
confidence: 64%
“…The best examples are Akt isoforms ( 52,135 ), IRS-1, IRS-2 ( 52, 68, 69 ), Grb14 ( 157 ), Evictin-1 ( 202 ), PHR1 ( p leckstrin h omology domain r etinal protein) ( 203,204 ), and recently identifi ed Akt dephosphorylating enzymes PHLPP (PH domain and leucine rich repeat protein phosphatases) and PHLPPL (PH domain and leucine rich repeat protein phosphatase-like) ( 205 ). Deletion of two PI-binding proteins, Akt2 ( 135 ) and IRS-2 ( 69 ), in the retina results in photoreceptor degeneration.…”
Section: Phosphoinositides In Cellular Regulationmentioning
confidence: 99%
“…In the cochlea PHR1 is also expressed in a subset of interdental cells at the surface of the spiral limbus (Xu et al, 2004). Immunohistochemistry and chemical extraction studies on the photoreceptor outer segment have shown that PHR1 is an integral membrane protein (Xu et al, 1999). PHR1 contains an N-terminal pleckstrin homology domain (Krappa et al, 1999;Xu et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 71 clones by histidine nutritional selection and β-galactosidase (β-gal) activity. The inserts from the isolated clones were sequenced, leading to the identification of four overlapping clones that encode the C-terminal region of a protein named PHR1 (Krappa et al, 1999;Xu et al, 1999) (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation